"Go West, Young Man, Go West!"? - Peter Bushnell; Wai Kin Choy (New Zealand Government, The Treasury, 2001)
Will economic integration lead to skilled citizens being drawn to the larger, richer economic partner? In 1983, Australia and New Zealand signed the Closer Economic Relations Agreement to ensure free trade in goods and services. Was this a modern equivalent of Horace Greeley's famous advice "Go West, young man, go West"? The evidence presented in this paper suggests that Greeley was right; many have indeed gone westward. However, a common labour market has not led to a brain drain. Paradoxically, the effect has been to increase the numbers of lower-skilled migrants from New Zealand and those with higher skills who are older or are not within the approved occupational groupings. The Trans-Tasman picture is further complicated by migration to New Zealand from third countries sufficient to offset the outflow of New Zealand citizens. The imbalance in net migration from New Zealand toward Australia has led to policy tensions. These are discussed briefly.
Keywords: F22; O15; 330; international migration; brain drain